The philosopher history in six types - Smith, Justin E. H. (Princeton University Press, 2016)
The Philosopher does just that, providing a new way of looking at the history of philosophy by bringing to life six kinds of figures who have occupied the role of philosopher in a wide range of societies around the world over the millennia--the Natural Philosopher, the Sage, the Gadfly, the Ascetic, the Mandarin, and the Courtier.